Examining the Causal Relationship between Private Sector Credit Extended and Economic Growth in Namibia - Andreas .; J P S Sheefeni (Journal of Economics and Behavioral Studies, 2019)
The paper examined causality between Private Sector Credit Extension (PSCE) and Economic growth using quarterly data for the period 2000:Q1-2017:Q4, in Namibia. The variables employed were Gross Domestic Product (GDP), Private Sector Credit Extended, Broad Money Supply (M2) and lending rates. The study tested for stationarity in order to determine the order of integration. Furthermore, a co-integration test was conducted on different sets of variables to establish the long run relationship. Granger causality test was also conducted to establish the direction of the relationships between the variables. The results for the stationarity test showed a combination of different orders of integration. The co-integration test revealed a stable long-run relationship among the variables. The Granger causality test results revealed one-directional causality running from PSCE to GDP. Therefore, one can conclude that that change in private sector credit extended can help predict economic growth.